2012
DOI: 10.1002/art.34638
|View full text |Cite
|
Sign up to set email alerts
|

In vivo bone‐specific EphB4 overexpression in mice protects both subchondral bone and cartilage during osteoarthritis

Abstract: Objective. In vitro activation of the receptor EphB4 positively affects human osteoarthritis (OA) articular cell metabolism. However, the specific in vivo role of this ephrin receptor in OA remains unknown. We investigated in mice the in vivo effect of bone-specific EphB4 overexpression on OA pathophysiology.Methods. Morphometric, morphologic, and radiologic evaluations were performed on postnatal day 5 (P5) mice and on 10-week-old mice. Knee OA was induced surgically by destabilization of the medial meniscus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 81 publications
1
36
0
1
Order By: Relevance
“…In spite of studies that report use of sham and operated knees in different mice 32,45 , there are also reports using sham and surgery-operated knees within the same animal 29,46 . Interestingly, in unpublished observations, we noted that the measurements of bone parameters of sham-operated knees differed depending on whether the contralateral knee was itself a sham or DMM-operated knee.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of studies that report use of sham and operated knees in different mice 32,45 , there are also reports using sham and surgery-operated knees within the same animal 29,46 . Interestingly, in unpublished observations, we noted that the measurements of bone parameters of sham-operated knees differed depending on whether the contralateral knee was itself a sham or DMM-operated knee.…”
Section: Discussionmentioning
confidence: 99%
“…OA was surgically induced in 10-week-old control and mTOR KO male mice by DMM or sham surgery (control) in the right knee, as previously described 18 19. Histological and biochemical analysis were performed at 5 and 10 weeks post-OA surgery.…”
Section: Methodsmentioning
confidence: 99%
“…[48][49][50][51][52][53][54] In the DMM OA model on C57BL/6 mice, the DMM induced mechanical allodynia and activity obstacle coincidently with cartilage injury was found after 15 weeks of DMM surgery. Similar results also demonstrated by other groups, 26,39,55) but in their research, the slight pathological change on cartilage was found 9 weeks after the DMM surgery, different from 15 weeks in our DMM model.…”
Section: Discussionmentioning
confidence: 99%